Designing novel inhibitors against cyclopropane mycolic acid synthase 3 (PcaA): targeting dormant state of Mycobacterium tuberculosis. Issue 17 (22nd November 2021) - Verma, Jyoti; Subbarao, Naidu
Abstract: Mycobacterium tuberculosis can sustain inside the host in dormant (non-replicating) state for years. It suppresses the host immune system by residing in the host alveolar macrophage, resulting in the development of latent tuberculosis. Despite many antibiotics available for the treatment of tuberculosis, the major hurdle in complete elimination is the ability of the bacilli to undergo dormancy and develop resistance against the existing drugs. Cyclopropanation of mycolic acids present in the cell wall of mycobacteria is required for its persistence and virulence. Cyclopropane synthases such as PcaA, CmaA1 and CmaA2, introduce site-specific modifications in mycolic acids. PcaA expression levels are high during dormancy and the gene mutants fails to persist, showing reduced survival in host macrophage. Hence, PcaA appears as a potential target to develop inhibitors against the dormant bacilli. In this study, we have identified compounds with maximum binding affinity against PcaA by in-silico virtual screening of anti-tuberculosis compounds and their structural analogues. In-silico docking followed molecular dynamic simulations and free energy calculations of the compounds with highest docking score in their respective libraries. This study reports novel inhibitors that can act as better anti-tuberculosis compounds targeting PcaA. Communicated by Ramaswamy H. Sarma